Adulthood Stressors, History of Childhood Adversity, and Risk of Perpetration of Intimate Partner Violence - Roberts, Andrea L. (2011)
BACKGROUND: Over half a million U.S. women and more than 100,000 men are treated for injuries from intimate partner violence (IPV) annually, making IPV perpetration a major public health problem. However, little is known about causes of perpetration across the life course. PURPOSE: This paper examines the role of “stress sensitization,” whereby adult stressors increase risk for IPV perpetration most strongly in people with a history of childhood adversity. METHODS: The study investigated a possible interaction effect between adulthood stressors and childhood adversities in risk of IPV perpetration, specifically, whether the difference in risk of IPV perpetration associated with past-year stressors varied by history of exposure to childhood adversity. Analyses were conducted in 2010 using de-identified data from 34,653 U.S. adults from the 2004–2005 follow-up wave of the National Epidemiologic Survey on Alcohol and Related Conditions. RESULTS: There was a significant stress sensitization effect. For men with high-level childhood adversity, past-year stressors were associated with an 8.8% increased risk of perpetrating compared to a 2.3% increased risk among men with low-level adversity. Women with high-level childhood adversity had a 14.3% increased risk compared with a 2.5% increased risk in the low-level adversity group. CONCLUSIONS: Individuals with recent stressors and histories of childhood adversity are at particularly elevated risk of IPV perpetration; therefore, prevention efforts should target this population. Treatment programs for IPV perpetrators, which have not been effective in reducing risk of perpetrating, may benefit from further investigating the role of stress and stress reactivity in perpetration.